Susan Stebbing's Logical Interventionism. Issue 2 (3rd April 2021) - Douglas, Alexander X.; Nassim, Jonathan
Abstract : We examine a contribution L. Susan Stebbing made to the understanding of critical thinking and its relation to formal logic. Stebbing took expertise in formal logic to authorise logical intervention in public debate, specifically in assessing of the validity of everyday reasoning. She held, however, that formal logic is purely the study of logical form. Given the problems of ascertaining logical form in any particular instance, and that logical form does not always track informal validity, it is difficult to see how she could justify her belief in logical interventionism. Her answer to this problem is the contribution we explore here. It involves the view that although the logician's expertise is not sufficient to assess arguments made in everyday contexts on its own, it nevertheless plays a unique role in giving systematicity and direction to the critique of such arguments, in particular, in public debate.